Whole-brain mapping of afferent projections to the bed nucleus of the stria terminalis in tree shrews. (1st October 2016) - Ni, Rong-Jun; Luo, Peng-Hao; Shu, Yu-Mian; Chen, Ju-Tao; Zhou, Jiang-Ning
Graphical abstract: Here we provided density of Fluoro-Gold (FG)-labeled cells in each brain structure of three tree shrews. The color of each box represents the relative density of labeled cells in each brain region, e.g., 0—no FG labeling, 1—sparse, 2—moderate, 3—extensive. Highlights: The first detailed whole-brain mapping of BST-projecting neurons in tree shrews. The BST-projecting regions were firstly identified in the tree shrew brain. The density of BST-projecting neurons in whole-brain regions was analyzed. Abstract: The bed nucleus of the stria terminalis (BST) plays an important role in integrating and relaying input information to other brain regions in response to stress. The cytoarchitecture of the BST in tree shrews ( Tupaia belangeri chinensis ) has been comprehensively described in our previous publications. However, the inputs to the BST have not been described in previous reports. The aim of the present study was to investigate the sources of afferent projections to the BST throughout the brain of tree shrews using the retrograde tracer Fluoro-Gold (FG). The present results provide the first detailed whole-brain mapping of BST-projecting neurons in the tree shrew brain. The BST was densely innervated by the prefrontal cortex, entorhinal cortex, ventral subiculum, amygdala, ventral tegmental area, and parabrachial nucleus. Moreover, moderate projections to the BST originated from the medial preoptic area, supramammillary nucleus, paraventricular thalamic nucleus, pedunculopontine tegmental nucleus, dorsal raphe nucleus, locus coeruleus, and nucleus of the solitary tract. Afferent projections to the BST are identified in the ventral pallidum, nucleus of the diagonal band, ventral posteromedial thalamic nucleus, posterior complex of the thalamus, interfascicular nucleus, retrorubral field, rhabdoid nucleus, intermediate reticular nucleus, and parvicellular reticular nucleus. In addition, the different densities of BST-projecting neurons in various regions were analyzed in the tree shrew brains. In summary, whole-brain mapping of direct inputs to the BST is delineated in tree shrews. These brain circuits are implicated in the regulation of numerous physiological and behavioral processes including stress, reward, food intake, and arousal.